The Influence of Emotions on the Endowment Effect - Otacílio Torres Vilas Boas (Revista Brasileira de Finanças, 2009)
According to prospect theory, individuals with loss aversion would tend to attribute a higher value to a good once their ownership over it had been established. Such tendency would cause reluctance to trade the good, even if an equivalent one were offered in exchange. Thaler (1980) named this phenomenon endowment effect. In this article, we present a review of the literature about the topic, which has been one of the most investigated themes in the relatively recent ﬁeld of behavioral ﬁnance. Adopting Knetsch’s research model (1989), we conducted two experiments in order to investigate the phenomenon in a Brazilian sample, speciﬁcally testing the inﬂuence of emotions on its manifestation. The results replicate ﬁndings for the endowment effect, and suggest that negative emotions attenuate the observed effects. Positive emotions, however, did not have any detectable inﬂuence over the phenomenon.